2020
DOI: 10.1186/s13195-020-00601-w
|View full text |Cite|
|
Sign up to set email alerts
|

Relevance of biomarkers across different neurodegenerative diseases

Abstract: Background: The panel of fluid-and imaging-based biomarkers available for neurodegenerative disease research is growing and has the potential to close important gaps in research and the clinic. With this growth and increasing use, appropriate implementation and interpretation are paramount. Various biomarkers feature nuanced differences in strengths, limitations, and biases that must be considered when investigating disease etiology and clinical utility. For example, neuropathological investigations of Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 91 publications
0
47
0
Order By: Relevance
“…Even if no causal treatments are available for these diseases, a reliable diagnosis as early as possible plays a major role in modulating the course of the disease through drug and non-drug therapies and enable patients to create a self-determined future. The establishment of validated biomarkers for AD and non-AD neurodegenerative disorders remains a major challenge (73).…”
Section: Discussionmentioning
confidence: 99%
“…Even if no causal treatments are available for these diseases, a reliable diagnosis as early as possible plays a major role in modulating the course of the disease through drug and non-drug therapies and enable patients to create a self-determined future. The establishment of validated biomarkers for AD and non-AD neurodegenerative disorders remains a major challenge (73).…”
Section: Discussionmentioning
confidence: 99%
“…Glial fibrillary acidic protein (GFAP) is an astrocyte marker; total tau (t-tau) and neurofilament-light chain (NF-L) are axonal markers, and ubiquitin carboxy-terminal hydrolase L1 (UCH-L1) is a neuronal marker. These markers are proposed as surrogate markers of neuronal (NF-L, t-tau, and UCH-L1) and neurovascular unit (GFAP) damage in conditions including, but not limited to, acute neurologic trauma and chronic neurodegenerative conditions such as Alzheimer disease ( 10 , 11 ).…”
mentioning
confidence: 99%
“…After controlling for possible confounders only the association of plasma NfL levels with CDRSoB changes in CN participants remained significant. Previous studies have reported plasma NfL levels to correlate with baseline cognition [ 3 7 , 29 31 ]. Of these studies, only two considered both CDR and MMSE scores [ 4 , 7 ], and a single study reported a correlation of plasma NfL levels with longitudinal MMSE change in cognitively impaired participants [ 3 ].…”
Section: Discussionmentioning
confidence: 99%